Purchasing Power Parity Of East Java Society - Mochamad Ardeanestu Sarwana; Ida Nuraini (SEAN Institute, 2024)
The development of the purchasing power index in East Java over the past few years, with a special focus on changes and their impact on workers' wages. Does the development of the Regional Minimum Wage, inflation and GRDP Per Capita Growth affect the purchasing power parity of the people of East Java? This study took data from the Central Bureau of Statistics which was processed using the Eviews 10 data processing application. The results showed that the three variables of UMR, GRDP per capita and inflation had a significant effect on the Purchasing Power Index in 29 districts and 9 cities in East Java Province.